Structural Moieties Required for Cinnamaldehyde-Related Compounds to Inhibit Canonical IL-1β Secretion - Su-Chen Ho; Yi-Huang Chang; Ku-Shang Chang (Molecules, 2018)
Suppressing canonical NOD-like receptor protein 3 (NLRP3) inflammasome-mediated interleukin (IL)-1β secretion is a reliable strategy for the development of nutraceutical to prevent chronic inflammatory diseases. This study aimed to find out the functional group responsible for the inhibitory effects of cinnamaldehyde-related compounds on the canonical IL-1β secretion. To address this, the suppressing capacities of six cinnamaldehyde-related compounds were evaluated and compared by using the lipopolysaccharide (LPS)-primed and adenosine 5′-triphosphate (ATP)-activated macrophages. At concentrations of 25~100 μM, cinnamaldehyde and 2-methoxy cinnamaldehyde dose-dependently inhibited IL-1β secretion. In contrast, cinnamic acid, cinnamyl acetate, cinnamyl alcohol and α-methyl cinnamaldehyde did not exert any inhibition. Furthermore, cinnamaldehyde and 2-methoxy cinnamaldehyde diminished expressions of NLRP3 and pro-IL-1β. Meanwhile, cinnamaldehyde and 2-methoxy cinnamaldehyde prevented the ATP-induced reduction of cytosolic pro-caspase-1 and increase of secreted caspase-1. In conclusion, for cinnamaldehyde-related compounds to suppress NLRP3 inflammasome-mediated IL-1β secretion, the propenal group of the side chain was essential, while the substituted group of the aromatic ring played a modifying role. Cinnamaldehyde and 2-methoxy cinnamaldehyde exerted dual abilities to inhibit canonical IL-1β secretion at both stages of priming and activation. Therefore, there might be potential to serve as complementary supplements for the prevention of chronic inflammatory diseases.